Strategi Guru dalam Mengajarkan Sejarah Kebudayaan Islam di MAN 2 Tabalong - Hatmiah Hatmiah (STIT Syekh Muhammad Nafis Tabalong, 2025)
Islamic Cultural History (ISCH) teaching in Islamic schools plays a crucial role in instilling Islamic values ​​and introducing students to the history of Islamic civilization. However, the challenges of delivering historical material, often perceived as monotonous, encourage teachers to employ more varied and meaningful learning strategies. This study focuses on teachers' strategies in teaching ISCH at MAN 2 Tabalong. The purpose of this study is to describe the learning strategies used by teachers and their impact on student engagement and understanding. This study employed a qualitative approach with descriptive methods. Data collection techniques included observation, in-depth interviews, and documentation of ISCH teachers and classroom learning activities. Data analysis was conducted inductively through data reduction, data presentation, and conclusion drawing. The results showed that teachers implemented various strategies such as interactive lectures, group discussions, and project-based learning. Teachers also linked the material to the local cultural context to enhance student relevance and interest. Despite constraints such as limited media and differences in student abilities, teachers demonstrated innovation through the use of simple media and task differentiation strategies. These strategies have been shown to increase student engagement and understanding of historical and Islamic values. These findings indicate that varied and contextual learning strategies are highly effective in teaching Islamic Studies (IS) at the madrasah level.